2018
DOI: 10.1016/j.kjms.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: And its role in breast cancer

Abstract: Vitamin D is a fat soluble vitamin that plays a role in calcium and phosphorus homeostasis. Recently, extensive research on its extraskeletal actions has linked vitamin D deficiency to an increased risk of infection, diabetes mellitus types 1 and 2, cardiovascular disease, obesity, asthma, inflammatory bowel disease, colon, breast, prostate and ovarian cancer and some neurological diseases. There are various mechanisms by which vitamin D influences the natural history of cancer. These include the role of vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 34 publications
1
48
0
1
Order By: Relevance
“…Vitamin D and the VDR have become a complex story with an evolving landscape, especially in the last few decades [4,5,9,12,18,19,44,45,46,47,48]. Deuster et al reviewed the importance of Vitamin D and its receptor in the pathogenesis of certain types of cancer such as colorectal, lung but mainly gynecological cancers, where they found the VDR to be upregulated, indicating its relevance for cancer etiology [46].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D and the VDR have become a complex story with an evolving landscape, especially in the last few decades [4,5,9,12,18,19,44,45,46,47,48]. Deuster et al reviewed the importance of Vitamin D and its receptor in the pathogenesis of certain types of cancer such as colorectal, lung but mainly gynecological cancers, where they found the VDR to be upregulated, indicating its relevance for cancer etiology [46].…”
Section: Discussionmentioning
confidence: 99%
“…Since vitamin D also exhibits antiproliferative and pro-differentiating properties, its deficiency has been correlated with the progression of several malignancies [ 70 , 215 , 216 , 217 , 218 , 219 ], especially breast [ 220 , 221 , 222 , 223 ], ovarian [ 224 , 225 ] and skin tumours [ 226 , 227 , 228 , 229 ].…”
Section: Vitamin D: State Of the Artmentioning
confidence: 99%
“…In the review by M. de La Puente-Yague et al in 2018, the authors suggest that the association of circulating 25-OH-D 3 with breast cancer risk differs mainly according to the menopausal status of the patient and the administered dose of vitamin D. Moreover, an inverse association was observed between 25-OH-D 3 level and breast cancer risk among postmenopausal women. The authors indicate that this correlation was more apparent when women showed a 25-OH-D 3 threshold of approximately 27 ng/mL [17]. Some of these women gained weight and developed obesity, which promotes an increase in circulating estrogens and enhances the risk of developing hormone-dependent breast cancer.…”
Section: Introductionmentioning
confidence: 99%